Structural, rheological and antioxidant properties of pectins from Equisetum arvense L. and Equisetum sylvaticum L. (1st April 2019) - Patova, O.A.; Smirnov, V.V.; Golovchenko, V.V.; Vityazev, F.V.; Shashkov, A.S.; Popov, S.V.
Graphical abstract: Highlights: Pectins from E. sylvaticum and E. arvense have similar structure. Horsetail pectins mainly composite of HG regions with minor low branched RG regions. Horsetail pectins are partially acetylated in low methyl-esterified HG regions. Pectin EA forms stronger ionotropic gel than pectin ES. Anti-DPPH activity of pectin EA is higher than pectin ES. Abstract: The pectins were isolated from sterile stems of E. arvense (EA, yield 5.9%) and E. sylvaticum (ES, yield 4.8%) (Equisetaceae) using ammonium oxalate extraction after preliminary treatment with dilute HCl (рH 4.0). The pectins possessed high molecular weight (Mw, 340–360 kDa), high GalA content (ca. 85%), low degrees of methyl-esterification (14–16%) and acetylation (3–8%). NMR analysis indicated extensive regions of partially methyl-etherified and 3- O -acetylated HG and minor regions of low branched RG in the fragment isolated after hydrolysis of pectin EA by pectinase. Pectin EA produced a higher viscosity solution, formed a stronger and more rigid ionotropic hydrogel than pectin ES. The pectins scavenged DPPH and hydroxyl radicals, but not the superoxide radical and hydrogen peroxide. Phenolic compounds (0.11 and 0.23%) associated with polysaccharide moieties were apparently responsible for the differences in the anti-DPPH scavenging activity of pectins EA and ES (63 and 49%). The findings suggested that pectin from E. arvense should be more perspective than pectin from E. sylvaticum on their use as components of wound healing remedies.